Differential responses of Picea asperata and Betula albosinensis to nitrogen supply imposed by water availability. (16th May 2018) - Yin, Chunying; Palmroth, Sari; Pang, Xueyong; Tang, Bo; Liu, Qing; Oren, Ram
Abstract: A pot experiment was conducted to investigate the effects of nitrogen (N) addition (0, 20, 40 g N m −2 year −1, N0, N20, N40, respectively) on the growth, and biomass accumulation and allocation of coniferous and deciduous ( Picea asperata Mast. and Betula albosinensis Burk. ) seedlings under a range of soil moisture limitation (40%, 50%, 60%, 80% and 100% of field capacity, FC). At 100% FC, growth of shade-tolerant P. asperata increased with N supply, while that of shade-intolerant B. albosinensis reached a maximum at N20, declining somewhat thereafter. At 60% FC and lower moisture content, water availability limited the growth of P. asperata seedlings, while N availability became progressively limiting to growth with moisture increasing above 60% FC. The transition from principally water-limited response to N-limited response in B. albosinensis occurred at lower moisture content. For P. asperata, these patterns reflected the responses of roots, consistent with changes in root/shoot biomass. For B. albosinensis the response reflected changes in shoot dimensions and root biomass fraction, the latter decreasing with size and foliar [N]. We are not aware of another study demonstrating such differences in the shape of the growth responses of seedlings of differing potential growth rate, across a range in belowground resource supply. The responses of leaf photosynthesis (as well as photosynthetic water and N-use efficiencies) were consistent with the observed growth response of P. asperata to water and N availability, but not of B. albosinensis, suggesting that leaf area dynamics (not measured) dominated the response of this species. Betula albosinensis, a fast-growing species, has a relative narrow range of soil water and N availability for maximum growth, achieved by preferential allocation to the shoot as resources meet the requirements at moderate N and water supply. In contrast, P. asperata increases shoot biomass progressively with increasing resources up to moderate water supply, preferentially growing more roots when resources are not limiting, suggesting that its capacity to produce shoot biomass may reach a biological limit at moderate levels of resource supply.